Peraturan Daerah Tentang Penataan Pasar di Kabupaten Enrekang - Ismaya Ismaya; Yunus Busa; Elihami Elihami; Andi Ahmad Chabir Galib; Ushwa Dwi Masrurah Arifin Bando; Rahmat Rahmat (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Market dynamics, both traditional markets and modern markets, are essentially a link in the chain that connects producers and consumers, sellers and buyers, and between business actors and the consumer community. The market plays an important role in the economy, because prices are formed in the market. The traditional market segment has a threat when the modern market dominates and the traditional market cannot compete, namely turning off traditional stalls because it changes consumer habits. Adjacent position between supermarkets, hypermarkets or minimarkets through the advantages they have compared to traditional markets. Along with this, it is necessary to issue a regional regulation for market management. The team from Muhammadiyah Enrekang University then followed up on this in community service activities. This community service activity was carried out as an effort to support the Regional Government of Enrekang Regency in producing Regional Regulations. The activity was carried out offline for seven (7) months, from March to October 2022. The result of this activity was the birth of the Enrekang Regency Regional Regulation Concerning Market Management.